Bioremediation of water contaminated with heavy metals using chicken feathers in the ite wetlands, Tacna, Perú (Agroindustrial Science, 2026)
The objectives of this study were: 1) to determine the effect of the treatment (broiler chicken feathers) at different proportions on copper removal, 2) to determine the effect of the treatment (broiler chicken feathers) at different proportions on iron removal, and 3) to estimate the degree of association between the removal of metal ions (copper and iron). Convenience sampling was performed at 5 points, with 3 replicates and 3 treatments (control, 4 g/L, and 8 g/L). Statistical analysis was performed using ANOVA, Tukey's test, and Spearman's rho correlation. The treatment with a dose of 4 grams of feathers/liter showed the greatest copper removal at 69.4%. Similarly, the same treatment also showed the greatest iron removal at 93.1%. The degree of association between the removal of copper and iron metal ions using broiler chicken feathers is not statistically significant. Chicken feathers are a natural adsorbent that has proven effective in remediating water contaminated with heavy metals. Keratin-based biomaterials have enormous potential in the bioremediation of water contaminated with heavy metals.
Keywords: Adsorption; copper; iron; keratin; removal; remediation